2018
DOI: 10.1038/s41598-018-23650-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal deformation patterns of the Lake Urmia Causeway as characterized by multisensor InSAR analysis

Abstract: We present deformation patterns in the Lake Urmia Causeway (LUC) in NW Iran based on data collected from four SAR sensors in the form of interferometric synthetic aperture radar (InSAR) time series. Sixty-eight images from Envisat (2004–2008), ALOS-1 (2006–2010), TerraSAR-X (2012–2013) and Sentinel-1 (2015–2017) were acquired, and 227 filtered interferograms were generated using the small baseline subset (SBAS) technique. The rate of line-of-sight (LOS) subsidence of the LUC peaked at 90 mm/year between 2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Although SBAS is a technique, it can also be considered as an algorithm for SAR processing too. Previous studies revealed that SBAS was an effective technique to monitor land subsidence in Iran [30][31][32][33][34][35]52]. Here, we follow the SBAS InSAR method introduced by Berardino et al to derive mean velocity displacement values.…”
Section: Sbas Time Series Analysismentioning
confidence: 99%
“…Although SBAS is a technique, it can also be considered as an algorithm for SAR processing too. Previous studies revealed that SBAS was an effective technique to monitor land subsidence in Iran [30][31][32][33][34][35]52]. Here, we follow the SBAS InSAR method introduced by Berardino et al to derive mean velocity displacement values.…”
Section: Sbas Time Series Analysismentioning
confidence: 99%
“…New satellite constellations of SAR missions such as Cosmo-SkyMed, TerraSAR-X, and ALOS-2 can guarantee high-resolution SAR data for different applications. SAR interferometry (InSAR) is a powerful technique that uses the phase and amplitude information of at least two SAR images with the same geometry and characteristics to extract the displacement rate of earthquakes [19][20][21][22][23][24][25][26], ground subsidence [14][15][16][17][18], volcanic activity [27][28][29][30], mining activities [7,31], structures [32][33][34], and landslides [35][36][37][38][39][40][41][42]. The technique enables us to overcome the challenges of conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are more processes related to irrigation and reduced water availability that might lead to unusable agricultural land, such as degradation of soils (e.g. salinization) 55 , subsidence 47,78 , desertification 79,80 , and sink hole formation because of lowered groundwater tables 81,82 . Until recently, the share of degrading crop areas in the wetter northwest of Iran is rather low, however it might increase in the future if water will continue to be used as unsustainably as in the last decades.…”
Section: Agricultural Areas and Associated Vegetation Growthmentioning
confidence: 99%